Cloud-Based ERP Implementation in SME’s: A Literature Survey - Jaafar Mohammed, Ghaith; Burhanuddin, MA (International Journal of Engineering and Technology, 2018)
Cloud based Enterprise Resource Planning (ERP) can be instantly deployed as it does not need a high upfront investment. These enterprise systems are substitutes to on-premises ERP systems. Cloud ERP also known as SaaS (Software-As-Service) ERP. Current studies show that there are many organizations have been adopting cloud ERP recently. They have observed the welfares and opportunities offered by cloud computing. This paper aims to provide a detailed overview on the benefits, opportunities, and advantages of cloud ERP. This paper would be useful for future adopters and decision makers of cloud ERP in SMEs.